POSSIBLE ORIGIN OF NEMIANA SIMPLEX PALIJ IMPRINTS - Mienasova, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nemiana simplex Palij is the most prevalent form of Ediacaran fauna in Podolia region. Imprints are round convex discs with smooth surface and are considered to be the remains of soft-bodied organisms. They led attached mode of life and were buried in situ. Nemiana remains are known from Vendian sequences of Podolia region, Yorga Formation of the White Sea area, Olenek uplift in the Siberian Platform, in Upper Precambrian deposits of Canada, China and Australia. Near Kaniv State Nature Reserve the author observed the formations, which look like modern "nemiana". Bottom of the microbays is covered with little sand hillocks. Their diameter is 3-8 mm and height is to 3 mm. Sand thickness is 2-4 mm. There is aleurite clay under the sand layer with peculiar hydrogen sulphide smell. These hillocks are, probably, the result of microbial mats life activity. These mats were formed by a lot of different microorganisms. Author considers Nemiana simplex Palij to have been formed the same way as stromatolites: mat surface is gradually covered with sand when the water level changes. And microorganisms either migrate up through the sediment layer, which accumulates, or temporarily pass into latent state with consequent recolonization of the sediment. As a result, the sediment is structured, as in the case of stromatolites, it becomes layered. As a colony dies, the external zone of the matrix behaves for some time as a hollow envelope. And, it can be preserved in fossil condition as a discoidal imprint or, if sediment penetrates inside, a three-dimensional mold.
Keywords: nemiana; Vendian; Ediacaran fauna; Podolia region; microbial mat